Sleep Disturbances in Pediatric Bipolar Disorder: A Comparison between Bipolar I and Bipolar NOS - Baroni, Argelinda; Hernandez, Mariely; Grant, Marie; Faedda, Gianni (Frontiers in Psychiatry, 2012)
Introduction: The diagnosis of Bipolar Disorder (BD) in youths has been controversial, especially for the subtype BD Not Otherwise Specified (BD-NOS). In spite of growing evidence that sleep is a core feature of BD, few studies characterize and compare sleep disturbances in youth with BD type I (BD-I) and BD-NOS. Sleep disturbances are frequently reported in clinical descriptions of children and adolescents with BD, however the reporting of the frequency and characteristics of sleep symptoms in youth with BD NOS and BD I during episodes remain poor. This study compares symptom of sleep disturbance as occurring in manic and depressive episodes in BD I and BD NOS youth using KSADS-PL interview data. The study also addresses whether symptoms of sleep disturbance vary in different age groups. Material and Methods: The sample consisted of 70 children and adolescent outpatients at an urban specialty clinic (42M/28F, 10.8±3.6 years old) including 24 BP-I and 46 BP-NOS assessed using K-SADS-PL-parent interview. Results: Sleep disturbances including insomnia and decreased need for sleep were reported by 84.3% of the sample. Enuresis was diagnosed in 27% of sample. There were no significant differences in frequency of sleep symptoms between BD-I and BD-NOS. Regardless of BD subtype, current functioning was negatively correlated with decreased need for sleep but not insomnia, and regardless of BD subtype. Conclusion: The majority of youth with BD presents with sleep symptoms during mood episodes. BD NOS presents with the same proportion of sleep symptoms as BD I in our sample.